2019
DOI: 10.1007/s11248-019-00154-1
|View full text |Cite
|
Sign up to set email alerts
|

Meeting report of the OECD conference on “Genome Editing: Applications in Agriculture—Implications for Health, Environment and Regulation”

Abstract: The “OECD Conference on Genome Editing: Applications in Agriculture—Implications for Health, Environment and Regulation” was held on the 28–29 June 2018 at the OECD headquarter and conference centre in Paris, France. It brought together policy makers, academia, innovators and other stakeholders involved in the topic, in order to take stock of the current technical developments and implementations of genome editing, as well as their applications in various areas of agriculture and the implications they give ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 81 publications
0
21
0
1
Order By: Relevance
“…Genome engineering is still in its infancy, equivalent to when the Apple App Store had about one hundred choices rather than the millions today. Regulatory policy makers are stuck in innumerable process-oriented meetings that involve hundreds of individuals and organizations that are dependent on stagnation as they focus on legal minutiae while missing what the future portends, e.g., the 2019 Organization for Economic Co-operation and Development conference on GE [146] . If changes in regulatory policies of Genapps are to be made, they need to be Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Genome engineering is still in its infancy, equivalent to when the Apple App Store had about one hundred choices rather than the millions today. Regulatory policy makers are stuck in innumerable process-oriented meetings that involve hundreds of individuals and organizations that are dependent on stagnation as they focus on legal minutiae while missing what the future portends, e.g., the 2019 Organization for Economic Co-operation and Development conference on GE [146] . If changes in regulatory policies of Genapps are to be made, they need to be Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The term genetically modified refers to plants whose genome has been modified in a way that would not have been occurred naturally (Wang et al, 2016b;Duensing et al, 2018;Friedrichs et al, 2019).…”
Section: Regulation Of Genome-edited Cropsmentioning
confidence: 99%
“…The Food Safety and Standards Authority of India define genetically engineered or modified food as "any food or food ingredient composed or containing genetically modified or engineered organisms obtained through modern biotechnology, or food and food ingredients produced from but not containing genetically modified or engineered organisms obtained through modern biotechnology". Thus all new technologies including CRISPR-Cas9 gene technologies (including genome editing) are still regulated within the existing regulatory framework (Friedrichs et al, 2019).…”
Section: Regulation Of Genome-edited Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…The license fees for intellectual property could restrict the ability of small-and medium-sized enterprises to commercialize their genome-edited crops. Therefore, to further advance the field of genome editing research for crop commercialization, it is suggested that reasonable licensing fees be imposed (Friedrichs et al, 2019).…”
Section: Current Status For the Quality Improvement Of Crops By Genommentioning
confidence: 99%